The effects of computer-aided concept cartoons and outdoor science activities on light pollution - Güliz Aydın (International Electronic Journal of Elementary Education, 2015)
The purpose of this study is to create an awareness of light pollution on seventh grade students via computer aided concept cartoon applications and outdoor science activities and to help them develop solutions; and to determine student opinions on the practices carried out. The study was carried out at a middle school in Muğla province of Aegean Region in Turkey. It was single group pre test-post test model that was used in the study. The data in the study were collected via open-ended questions about light pollution and semi-structured interview questions. Open ended questions about light pollution were applied on students as a pre-test and post-test. After the post-test was applied, semi-structured interviews were carried out with students. The qualitative analysis of the data collected from the open-ended questions and semi-structured interview questions were made and student expressions were quoted. After the implementations, it was found that there was an increase in the correct answers of students on light pollution. Also, all students interviewed stated positive opinions regarding the implementations. The implementations carried out are convenient for students to develop an awareness of the ecological, astronomics and economical results of light pollution and to develop solutions for preventing light pollution.